Analisis Ketidakberaturan Struktur Horizontal dan Vertikal Tower Mesjid Rahmah Kota Langsa Menggunakan SNI 1726:2019 - Muhammad Riswandy; Haikal Fajri; Muhammad Zacky Ardhyan; Awalu Rahman (INSOLOGI: Jurnal Sains dan Teknologi, 2025)
This study aims to analyze the response of a high-rise building to horizontal and vertical structural irregularities in a multi-story structure. The subject of the study is the Rahmah Mosque Tower, located at Jl. Lilawangsa, Gampong Paya Bujuk Tunong, Langsa Baro District, Langsa City, Aceh. This tower exhibits both horizontal and vertical irregularities, which can influence its behavior under applied lateral and vertical loadsThe structural behavior is evaluated by examining the building’s response to horizontal and vertical irregularities effect induced by seismic loading. The method for seismic loads are analyzed using dynamic response spectrum analysis in accordance with SNI 1726:2019, implemented in ETABS v18.1.1. Results indicate that failure in the Rahmah Mosque Tower is governed by beam collapse due to insufficient flexural capacity under seismic forces, whereas the columns are adequate to resist earthquake loads. Horizontally, the tower exhibits Type 1b and Type 1a irregularities, as well as Horizontal-Torsional Irregularity. Type 1a. Vertically, it displays Mass (weight) Irregularity and Vertical Geometric Irregularity. These irregularities could significantly affect a building's safety, stability, and structural efficiency. Designs that fail to calculate these irregularities may pose serious risks of damage, both under static and dynamic conditions.